Recurrence of Achilles tendon injuries in elite male football players is more common after early return to play: an 11-year follow-up of the UEFA Champions League injury study - Gajhede-Knudsen, M.; Ekstrand, J.; Magnusson, H.; Maffulli, N. (British Journal of Sports Medicine, 2013)
Background There is limited information about Achilles tendon disorders in professional football.Aims To investigate the incidence, injury circumstances, lay-off times and reinjury rates of Achilles tendon disorders in male professional football.